Urea Conversion for Low‐Temperature Selective Catalytic Reduction in a Swirled Diesel Exhaust Gas Configuration. Issue 4 (23rd February 2022) - Gierth, Sandro; Hartl, Sandra; Pollack, Martin; Hasse, Christian; Hofmann, Uwe; Zikoridse, Gennadi; Rautenberg, Helge; Will, Frank; Hahn, Christoph; Kureti, Sven
Abstract: A novel design of an AdBlue mixing unit to reduce urea deposits at low temperatures in diesel exhaust is described. The main principle of the mixer includes the injection of AdBlue in an axisymmetric swirling flow, which is achieved by splitting the exhaust stream and off‐centred introduction of the sub‐flows. Crucial geometric parameters were analyzed by computational fluid dynamics (CFD) simulations towards pressure loss, flow field, and spray morphology. Deposit formation was experimentally investigated on three upscaling levels implying an optical test bench, a diesel engine test bench, and a hydraulic excavator. In particular, the studies with the hydraulic excavator showed neither deposits nor critical back pressure. Overall, the experiments substantiated the working principle of the AdBlue mixer. Abstract : A mixing unit was designed for the AdBlue injection into diesel exhaust aiming at deposit reduction at low temperatures. The working principle is based on an axisymmetric swirling flow established by splitting the exhaust gas stream and introducing an off‐centred flow into the mixing unit. The mixing unit was designed by CFD simulations and transferred to three experimental upscaling levels.